2022
DOI: 10.30541/v47i4iipp.471-486
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth and Its Determinants in Pakistan

Abstract: Economically developed countries have been able to reduce their poverty level, strengthen their social and political institutions, improve their quality of life, preserve natural environments and achieve political stability [Barro (1996); Easterly (1999); Dollar and Kraay (2002a); Fajnzylber, Lederman, et al. (2002)]. After the World War II, most of the countries adopted aggressive economic policies to improve the growth rate of real gross domestic product (GDP). The neoclas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 58 publications
5
20
0
Order By: Relevance
“…The impact of FDI and R variables are negative but FDI is found statistically insignificant at 5% level. The result of this study is consistent with Afzal (2007) and Roy (2012) and Ali et al, (2013Ali et al, ( & 2015 contradicts with the findings of Shahbaz et al (2008).…”
Section: 2supporting
confidence: 91%
“…The impact of FDI and R variables are negative but FDI is found statistically insignificant at 5% level. The result of this study is consistent with Afzal (2007) and Roy (2012) and Ali et al, (2013Ali et al, ( & 2015 contradicts with the findings of Shahbaz et al (2008).…”
Section: 2supporting
confidence: 91%
“…Shahbaz et al. () used quarterly data of Pakistan over the period 1991‐2007 and found a positive relationship in growth and remittances. Financial development had a positive while trade openness endorsed negative impact on growth.…”
Section: Theoretical and Empirical Review Of Literaturementioning
confidence: 99%
“…() are complimented by Shahbaz et al . () and Shahbaz (). Jalil and Feridun () reported that financial development, capitalization and trade openness increase economic growth but real interest rate declines it.…”
Section: Literature Reviewmentioning
confidence: 99%